2017
DOI: 10.1108/ir-07-2016-0186
|View full text |Cite
|
Sign up to set email alerts
|

Study on dual peg-in-hole insertion using of constraints formed in the environment

Abstract: Purpose The purpose of this paper is to develop a dual peg-in-hole insertion strategy. Dual peg-in-hole insertion is the most common task in manufacturing. Most of the previous work develop the insertion strategy in a two- or three-dimensional space, in which they suppose the initial yaw angle is zero and only concern the roll and pitch angles. However, in some case, the yaw angle could not be ignored due to the pose uncertainty of the peg on the gripper. Therefore, there is a need to design the insertion stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Similar observations were reported by Liu and Carpin who showed that the convergence time for grasp planning was positively correlated while the probability of force closure was negatively correlated with increasing positional uncertainty [30]. Therefore, these active control techniques, as well as other, passive or hybrid compliance strategies [31][32][33][34][35], will still benefit from improved accuracy of the object's pose in the robot's frame.…”
Section: Related Worksupporting
confidence: 79%
“…Similar observations were reported by Liu and Carpin who showed that the convergence time for grasp planning was positively correlated while the probability of force closure was negatively correlated with increasing positional uncertainty [30]. Therefore, these active control techniques, as well as other, passive or hybrid compliance strategies [31][32][33][34][35], will still benefit from improved accuracy of the object's pose in the robot's frame.…”
Section: Related Worksupporting
confidence: 79%
“…Researchers have made efforts to use contact model based strategies to solve a wide range of peg-in-hole assembly problems with special requirements and high complexity in autonomous industrial manufacturing. For instance, the best methods for performing high-precision assembly [2] [12] [13] and large-scale component assembly [14] [4] [3] with the limited sensors have been widely investigated. Additionally, methods for deriving an assembly control strategy that can cope with complicated multiple peg-in-hole assembly flexibly has attracted considerable attention from researchers [1] [15] [16].…”
Section: A the Development Of Robotic Peg-in-hole Assemblymentioning
confidence: 99%
“…R OBOTIC assembly as the essential components of industrial applications has been studied for a long time. In this work, we look at the most common problem of robotic assembly: peg-in-hole assembly, which is the basis of a wide range of component assemblies [1] [2]. Robotic peg-in-hole assembly has been extensively researched and applied in various fields from large-scale object assembly, such as aviation components [3] [4], engines [5] and windshields assembly to small-scale components, such as mold casting manufacturing [6], electronic components [7] and even microproduct [8] assembly.…”
Section: Introductionmentioning
confidence: 99%
“…The robotic peg in hole application has been widely studied (Su et al , 2017). The most important aspect is to deal with the misalignment between mating connectors.…”
Section: Related Workmentioning
confidence: 99%